The Influence of Digital Technology and Green Economy on Taxpayer Awareness - MARBUN, Dick Wolters; BUTARBUTAR, Parulian Januar (Journal of Governance, Taxation and Auditing, 2025)
This study aims to explore the influence of digital technology and green economy on taxpayer awareness, as well as the role of green economy in mediating the influence between digital technology and taxpayer awareness in 100 respondents from the surrounding community and extended families selected using simple random sampling techniques, using questionnaires with a quantitative approach. The data processing method used in this study was carried out in two stages, namely the outer model and inner model, using SEM-PLS 4. The results of the study that have been obtained indicate that 1) Digital technology variables have succeeded in providing a significant influence on green economy 2) Digital technology variables have not succeeded in providing a significant influence on taxpayer awareness 3) Green economy variables have succeeded in providing a significant influence on taxpayer awareness 4) Green economy variables have succeeded in mediating the influence of digital technology on taxpayer awareness.